Dynamic lattice distortion in metallic nanocrystals. (15th January 2023) - Leonardi, Alberto; Leoni, Matteo
Abstract: Advanced design of metallic nanocrystals (NCs) for plasmonic applications requires control of the dynamic lattice distortion. Here we apply atomistic simulations coupled with total scattering to study the lattice vibrations induced by the thermal motion of atoms in Pd NCs. Quantitative analysis of the dynamic-relative displacement of neighbor atoms details the correlation of the lattice vibrations fading with the increase of atom-pair distance. Negative correlations are revealed from displacements of far-neighbor atoms with pair direction normal to the crystal surface, which we explain as breathing vibration modes. We propose a phenomenological dynamical model to predict the influence of material structure and NCs shape on the dynamic lattice distortion. Lattice vibrations show a marked dependence on the atom-pair direction, which enhances with decreasing size and cubic shape of crystals. Our work demonstrates that, if proper distortion models are used, the thermal motion of atoms near the surface of metallic NCs can be observed from total scattering data. Further simulations and experiments will support the future extension to compositionally and architecturally complex nanoparticles of the anisotropic lattice distortion model (ALDi) that is here introduced. Graphical abstract: Image, graphical abstract